The Business Value of Digital Transformation in the Tourism Industry: A Multi-Country Comparison - Hassanin, Sara (2025)
A Master of Business Administration (MBA) thesis by Sara Hassanin entitled, “The Business Value of Digital Transformation in the Tourism Industry: A Multi-Country Comparison”, submitted in April 2025. Thesis advisor is Dr. Taisier A. Zoubi. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).